2020
DOI: 10.25248/reas.e4655.2020
|View full text |Cite
|
Sign up to set email alerts
|

Perfil dos atendimentos de um serviço móvel de urgência e emergência de uma universidade federal

Abstract: Objetivo: Caracterizar o perfil dos atendimentos de um serviço móvel de urgência e emergência de uma Universidade Federal do interior do Estado do Rio Grande do Sul. Métodos: Estudo quantitativo, descritivo, retrospectivo, que utilizou-se de dados secundários, coletados de fichas de atendimento no período de maio de 2017 a abril de 2018. Os dados foram digitados em planilha no Excel e analisados por meio do software Statistica 13.3. Resultados: A população atendida foi predominantemente de estudantes do sexo f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
1
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 0 publications
1
1
0
3
Order By: Relevance
“…When analyzing the outcome of hospitalization, the study showed that most of the attendances were characterized by hospital discharge in a study developed in a private emergency room in southern Brazil, where most of the users were discharged after care (Hehn;Bueno, 2020). These same results were also evidenced in a study conducted in a mobile urgency and emergency service of a federal university, where the most prevalent outcome of care was the return to home (Cogo et al, 2020) Also from the same perspective, it was found that "observation followed by discharge" had a considerable prevalence, followed by "referral to other health services", also seen in the study by Medeiros et al (2023), where a transfer rate to other health services of 35.83% was identified. The hospitalization rates also showed a considerable number for the mixed health unit, unlike the deaths, which totaled 13 throughout the year.…”
Section: Resultssupporting
confidence: 69%
See 1 more Smart Citation
“…When analyzing the outcome of hospitalization, the study showed that most of the attendances were characterized by hospital discharge in a study developed in a private emergency room in southern Brazil, where most of the users were discharged after care (Hehn;Bueno, 2020). These same results were also evidenced in a study conducted in a mobile urgency and emergency service of a federal university, where the most prevalent outcome of care was the return to home (Cogo et al, 2020) Also from the same perspective, it was found that "observation followed by discharge" had a considerable prevalence, followed by "referral to other health services", also seen in the study by Medeiros et al (2023), where a transfer rate to other health services of 35.83% was identified. The hospitalization rates also showed a considerable number for the mixed health unit, unlike the deaths, which totaled 13 throughout the year.…”
Section: Resultssupporting
confidence: 69%
“…However, some studies have shown the predominance of males in urgent and emergency care in cases of urban violence. In terms of age, it is usually between 21 and 30 years old (Cogo et al, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…Para efetivar essa estrutura pré-hospitalar, o Samu foi incorporado como uma das portas de entrada do Sistema Único de Saúde (SUS), em 2003, pela portaria n. 1.863/2003. Entretanto, somente com o decreto n. 5.055/2004 o programa foi instituído em municípios e regiões do território nacional (Padilha et al, 2018;Cogo et al, 2020).…”
Section: Introductionunclassified
“…Já outro estudo realizado em Rio Grande do Sul em 2020 num período de 12 meses, observou um total de 940 atendimentos, sendo eles 593 (63,09%) atendimentos prestados ao gênero feminino e 347 (36,91%) ao masculino. Ao analisar as causas predominante nesse estudo identificou-se as situações clínicas com 81,8% e traumáticas contabilizando 18,2 % 7 .…”
Section: Introductionunclassified
“…Este profissional integra, lidera e é responsável por desenvolver atividades educacionais, organizar e planejar a assistência ao paciente, compondo também a equipe de atendimento da unidade de suporte avançado. Cabe ao enfermeiro conhecer a sua equipe de atendimento préhospitalar bem como conhecer a realidade local e regional e o tipo de atendimento prestado e requerido ao serviço do SAMU 3,7 .…”
Section: Introductionunclassified